A comparative analysis of influenza virus infections in the 2013/2014 and 2014/2015 epidemic seasons in the reporting system, for different age groups in Poland - Hallmann-Szelińska, Ewelina; Rabczenko, Daniel; Bednarska, Karolina; Kondratiuk, Katarzyna; B. Brydak, Lidia (Family Medicine & Primary Care Review, 2016)
Background . Influenza remains the cause of many seasonal infections, leading even to death, in all age groups, for all patient health states, under all health policies, and in all latitudes. Influenza infection needs to be thought of not only in terms of the loss of health and the exacerbation of existing diseases, but also in terms of the quantifiable financial consequences borne by the state. Objectives . The aim of the study was to compare two influenza seasons: 2013/14 and 2014/15 through an analysis of the number of samples in different age groups, collected on a weekly basis for 52 weeks, and to interpret the results in terms of type and subtype. Material and methods. Virological and epidemiological data were obtained from the SENTIN EL and NON -SENTIN EL programs. Virological tests were performed using RT-PCR and multiplex RT-PCR biological molecular methods. Results . The maximum number of confirmed cases of influenza coincides in time with the maximum number declared cases and suspected cases of influenza and influenza-like viruses. The peak occurrence of influenza-like virus detection was earlier than the peak detection of influenza virus. In the 2014/15 influenza season, significant differences in the percentage of positive samples were observed between the 5–9 and 10–14 age groups. During the 2013/14 influenza season, there was no statistically significant difference in the percentage of positive samples between the 15–25, 26–44, and 45–64 year old age groups. Conclusions . A new division of age groups allows more accurate assessment of the incidence of influenza and influenza-like illnesses and can assist health workers in preventing multiorgan influenza-related complications and deaths.